Extraterritorial Jurisdictions: Implementation of Foreign Public Officials in United States, United Kingdom, and Indonesia - Ginting, Jamin; Fadjar, Raden Febriarto; Talbot, Patrick (UI Scholars Hub, 2025)
Cross-border business transactions have the potential to be corrupted, especially in the form of bribery committed by actors from different countries and within different jurisdictions. The Indonesian Corruption Law has not regulated how to criminalize Indonesian public officials or certain private companies who bribe officials in other countries or vice versa. Although Indonesia has ratified the United Nation Convention Against Corruption, it has not adopted provision on bribery of foreign public officials. Among the international community, the regulations for bribery of foreign public officials have been started by the US Foreign Corrupt Practices Act of 1977. The United Kingdom also has an international bribery law for British entities called the United Kingdom Bribery Act 2010. The research issue is the implementation of the bribery article to the providers and receivers, under the conditions that they are not Indonesian citizens and the crimes were done outside of Indonesia. By using normative legal research method, the authors expect to provide an overview of Indonesian legal arrangements regarding the bribery of foreign public officials in order to banish foreign bribery practices that involve Indonesians and foreigners.